2019
DOI: 10.1002/acm2.12716
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric effect of rotational setup errors in stereotactic radiosurgery with HyperArc for single and multiple brain metastases

Abstract: PurposeIn stereotactic radiosurgery (SRS) with single‐isocentric treatments for brain metastases, rotational setup errors may cause considerable dosimetric effects. We assessed the dosimetric effects on HyperArc plans for single and multiple metastases.MethodsFor 29 patients (1–8 brain metastases), HyperArc plans with a prescription dose of 20–24 Gy for a dose that covers 95% (D95%) of the planning target volume (PTV) were retrospectively generated (Ref‐plan). Subsequently, the computed tomography (CT) used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 31 publications
2
52
1
1
Order By: Relevance
“…This is to account for the effects of residual rotational uncertainties, which can have a more profound impact on targets located at greater distances from the isocenter [16]. Additionally, Sagawa et al found that rotational setup errors caused non-negligible underdosage of the PTV if uncorrected [17]. At our institution, the GTV to clinical target volume (CTV) margin is zero.…”
Section: Patient Population and Treatment Criteriamentioning
confidence: 86%
“…This is to account for the effects of residual rotational uncertainties, which can have a more profound impact on targets located at greater distances from the isocenter [16]. Additionally, Sagawa et al found that rotational setup errors caused non-negligible underdosage of the PTV if uncorrected [17]. At our institution, the GTV to clinical target volume (CTV) margin is zero.…”
Section: Patient Population and Treatment Criteriamentioning
confidence: 86%
“…Several studies have investigated inter-and intra-fraction patient movement through analysis of pre-and/or post-treatment imaging. 2, [4][5][6][7][8] Further, other studies have provided more granular intrafraction motion data through collection of x-ray images at a range of frequencies during treatment. [9][10][11][12][13] Many however are limited to small patient cohorts or provide only 3 Degrees of Freedom (DoF) or 4 DoF information, or other limited subsets unique to the aims of their experiment.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…For the single‐isocenter treatment technique, the reference dose distribution data were rotated around the isocenter at different introduced degrees of rotation: ±0.5°, ±1°, ±2°. Angular offsets of>±2° are not often encountered in a clinical setting and, therefore, excluded from this study. Rotations occurred around the x‐axis, y‐axis, and z‐axis independently, as well as around all three axes (DICOM coordinate system adopted throughout this study).…”
Section: Methodsmentioning
confidence: 99%
“…[29][30][31]38 However, in all of the above studies the corresponding dosimetric impact on organs at risk (OARs) was not examined. In a recent study, Sagawa et al 39 studied the dose-increase to the normal brain parenchyma but disregarded the effect on other critical structures such as the brainstem and the optic pathway. To our knowledge, the only work reporting on OAR-sparing focused on singletarget cranial SRS, where a small rotational error was found to have a significant dosimetric impact in cases with OARs in close proximity to the target volume.…”
Section: Introductionmentioning
confidence: 99%